Crossed 2D versus Slipped 1D π‐Stacking in Polymorphs of Crystalline Organic Thin Films: Impact on the Electronic and Optical Response. Issue 21 (12th August 2019) - Aliaga‐Gosalvez, María José; Demitri, Nicola; Dohr, Michael; Roldao, Juan Carlos; Park, Sang Kyu; Oh, Sangyoon; Varghese, Shinto; Park, Soo Young; Olivier, Yoann; Milián‐Medina, Begoña; Resel, Roland; Gierschner, Johannes
Abstract: Polymorphs of organic semiconductors are of great interest as they shed light to structure‐property relationships. The full X‐ray thin film structure analysis of two polymorphs (B, G) of an important n‐type semiconducting dicyano‐distyrylbenzene based small molecule (CN‐TFPA) is reported. Drastically different structures of the monotropic phases are revealed, that is an uncommon 2D crossed π‐stacked arrangement for the B‐phase versus a 1D slipped π‐stack for G. Both phases exhibit a layered structure in the (100) plane with high structural integrity, driven by the hydrophobic contacts of the terminal CF3 groups; as (100) coincides with the film surface, this allows for exfoliation by scotch tape. An in‐depth time‐dependent density functional theory (TD‐DFT) based quantum mechanics/molecular mechanics (QM/MM) study reveals all subsequent significantly differing optical and electronic responses which result from the different arrangements: the B film shows little excitonic interaction with strong blue fluorescence, amplified spontaneous emission (ASE), and good 2D n‐type transport. The G film forms H‐aggregates with strong green fluorescence, no ASE, and 1D n‐type charge transport. The established structure‐property relationships are seen as a crucial step for computer‐aided device analysis. Abstract : A prototype small‐molecule‐based highly luminescent n‐type semiconductor gives two drastically different layered thin film structures (B, G) that is an uncommon 2D crossed π‐stacked arrangement for B versus a 1D slipped π‐stack for G. Time‐dependent density functional theory based QM/MM calculations reveal all details of the subsequent, largely differing optical and electronic response.